Gender differences between body composition and physical activity among Faculty of Sports Science and Recreation students / Muhammad Danial Noor Hamidi, Nurul Najwa Aminul Mahzan and Noor Fatihah Ilias - Noor Hamidi, Muhammad Danial; Mahzan, Nurul Najwa Aminul; Ilias, Noor Fatihah (Universiti Teknologi MARA, 2021)
Physical activity was linked with lower risk of mortality and developing non -communicable diseases. Strong evidence shows that physical inactivity increases the risk of most chronic diseases, decreases life expectancy and it was widely reported as having unambiguous effect on obesity level. Physical inactivity and obesity are seen in both gender. Therefore, the purpose of this study was to identify the differences between physical activity level (PA) and body composition (BC) among male and female Faculty of Sports Science and Recreation students in Universiti Teknologi MARA (UiTM). The International Physical Activity Questionnaire Short Form (IPAQ-SF) was used to measure physical activity level and the InBody 270 machine was used to measure the body composition of participants. Based on the results obtained there was no significant differences of Body Mass Index (BMI) (p = 0.64), Waist to Hip Ratio (WHR) (p = 0.92), Physical Activity Level (PA) (p = 0.12) among male and female students. The present study confirms that there was no significant different between gender on BMI and WHR among university students. Being physically active reduce the risk of getting chronic diseases. Students must practice a healthy and active lifestyle as they were valuable assets of the university and they played an important role to ensure the development of the whole country.